REVIEW on Georgy Mamulia’s monograph “Imam Shamil and the national liberation struggle of the North-East Caucasus mountaineers in French Diplomatic reports from Tiflis”. Tbilisi: Georgian Foundation for Strategic Studies, 2022. 380 p., with ill. - Ancabadze, Urij Dmitrievic (History, Archeology and Ethnography of the Caucasus, 2024)
The recently published collection of documentary materials from the Archive of French Foreign Policy presents diverse information on the national liberation movement of the North-East Caucasus peoples. The intensive diplomatic correspondence, spanning from 1839 to 1859, comprises dispatches sent by French consuls in Tiflis to their superiors in Paris. These reports detail the primary events in the Caucasian War’s theater of operations in Dagestan and Chechnya, offering insights into Russian strategies and the activities of Imam Shamil and his allies. Analytical notes on the regional situation constitute a significant component of this diplomatic correspondence. The French diplomats’ information was based on credible sources. Scholarly commentaries accompanying the materials further emphasize their historical value.